2003
DOI: 10.1073/pnas.0237171100
|View full text |Cite
|
Sign up to set email alerts
|

Origin-specific unwinding of herpes simplex virus 1 DNA by the viral UL9 and ICP8 proteins: Visualization of a specific preunwinding complex

Abstract: Herpes simplex virus 1 contains three origins of replication; two copies of oriS and one of a similar sequence, oriL. Here, the combined action of multiple factors known or thought to influence the opening of oriS are examined. These include the viral originbinding protein, UL9, and single-strand binding protein ICP8, host cell topoisomerase I, and superhelicity of the DNA template. By using electron microscopy, it was observed that when ICP8 and UL9 proteins were added together to oriS-containing supertwisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…In herpes simplex virus type 1 (HSV-1), the origin binding protein UL9 is proposed to carry out this activity. UL9 is known to possess ATPase and helicase activities in addition to its origin (8,26). Genetic analysis showed that the conserved helicase motifs in UL9 are essential both in vivo and in vitro for viral DNA replication (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In herpes simplex virus type 1 (HSV-1), the origin binding protein UL9 is proposed to carry out this activity. UL9 is known to possess ATPase and helicase activities in addition to its origin (8,26). Genetic analysis showed that the conserved helicase motifs in UL9 are essential both in vivo and in vitro for viral DNA replication (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The recognition sequence for OBP, TTCGCAC, is highly conserved among alphaherpesviruses but differs from its counterpart in roseoloviruses (20). OBP binds cooperatively to oriS, and the assembly of a stable complex containing two OBP dimers on oriS as well as ICP8 has been visualized by electron microscopy (23). OBP alone can destabilize the AT-rich spacer sequence (24).…”
Section: Activation Of Origins Of Dna Replicationmentioning
confidence: 99%
“…OBP alone can destabilize the AT-rich spacer sequence (24). In the presence of ATP, the preinitiation complex will proceed to unwind DNA and generate stretches of ϳ300-bp single-stranded DNA (ssDNA) covered with ICP8 within 15 min on linear DNA (23).…”
Section: Activation Of Origins Of Dna Replicationmentioning
confidence: 99%
“…The unwinding of the DNA is inherent to the function of helicases such as RNA polymerase (9), the mismatch repair MutS proteins (10) and HSV-1 UL9 protein (11,12), and hence these helicases must track the DNA. However, in the case of restriction enzymes (13) and the chromatin remodelling Snf2 proteins (14), there is no functional requirement to unwind the DNA.…”
mentioning
confidence: 99%